(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article discusses atrial fibrillation, one of the most common types of cardiac arrhythmias. It explores the etiology, clinical manifestations, diagnostic methods, and treatment strategies of the condition. Special attention is given to the role of functional diagnostics in the identification and management of atrial fibrillation. The article also highlights the importance of early detection and appropriate therapeutic interventions to reduce the risk of complications such as stroke and heart failure. The purpose of this study is to enhance the understanding of atrial fibrillation among clinical practitioners and improve patient outcomes through timely and effective medical care.